Design of a self-leveling cam mechanism for a stair climbing wheelchair. (June 2017) - Quaglia, Giuseppe; Nisi, Matteo
Highlights: A new version of an electric stair-climbing wheelchair is proposed. The performances in term of static stability and user comfort have been improved. A cam mechanism has been introduced to cancel the seat oscillation. A parametric analysis on the cam mechanism has been conducted. Abstract: This paper presents a new version of Wheelchair.q, a wheelchair with stair climbing ability. The wheelchair is able to climb single obstacles or staircases thanks to a hybrid wheel-leg locomotion unit with a triple-wheels cluster architecture. The new concept presented in this work represents an improvement respect to previous versions. Through a different arrangement of functional elements, the wheelchair performances in terms of stability and regularity during movement on stair have been increased. In particular, attention has been paid to ensure a regular and comfortable motion for the user during stair climbing operation. For this reason, a cam mechanism has been introduced and designed with the aim to compensate the oscillation generated on the wheelchair frame by the locomotion unit rotation. A design methodology for the cam profile is presented. Moreover, a parametric analysis on the cam profile and on the mechanism dimensions has been conducted with the aim to find a cam profile with suitable dimensions and performances in terms of pressure angle and radius of curvature. Graphical abstract: